2007
DOI: 10.1590/s1806-83242007000200004
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic prevalence of root canal ramifications in a sample of root canal treatments in a Brazilian Dental School

Abstract: The aim of this study was to radiographically investigate the presence of root canal ramifications found after endodontic treatment, and to determine any relationship between their presence and the type of the auxiliary chemical substance used. The study evaluated 1,470 endodontic treatments performed by final year undergraduate students at the Dental School of Piracicaba, State University of Campinas (UNICAMP), SP, Brazil, during the period from 1998 to 2000. The X-rays taken during treatment were evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Apical delta : The low number of mandibular molars with an apical delta observed in this study is similar to what has been reported among Brazilians whereby 0.95% of treated teeth mandibular molars exhibited apical deltas [27]. In the Jordanian population [2], none of the examined mandibular molar teeth were found to have an apical delta.…”
Section: Discussionsupporting
confidence: 86%
“…Apical delta : The low number of mandibular molars with an apical delta observed in this study is similar to what has been reported among Brazilians whereby 0.95% of treated teeth mandibular molars exhibited apical deltas [27]. In the Jordanian population [2], none of the examined mandibular molar teeth were found to have an apical delta.…”
Section: Discussionsupporting
confidence: 86%